Obligaciones tributarias en la Empresa Colbapi S.A. en el periodo fiscal 2021. - Merchán Rodríguez, Maurie Jahir (2022)
Compliance with tax obligations is important within all types of organization, by virtue of the fact that when this duty required by the State is not fully complied with, it leads to facing tax sanctions or sometimes the suspension of commercial activities. Reason for which, the objective of the present investigation is to indicate the tax obligations that the company COLBAPI S.A had to comply with punctually in the fiscal period 2021. The line of investigation applied in the case study is Administrative, Tax, Audit and Control Financial Management. ; and the subline: Audit and Control. The methodology was made up of descriptive-deductive methods and documentary research was used. While the techniques were the interview through an internal control questionnaire and direct observation. The results of the investigation concluded that one of the main difficulties that the company COLBAPI S.A has is the cancellation of its tax obligations, which is due to the inadequate tax management of the personnel in charge of carrying out the declarations or lack of immediate liquidity. In addition, COLBAPI S.A. During the 2021 period, it did not adequately comply with the tax obligations regarding the declaration and payment of income tax and VAT due to the lack of liquidity derived from the health crisis that the country experienced. However, it has managed to stay in the market.